Lone Aortic Insufficiency and Conduction Disease: A Marker of Reactive Arthritis. Issue 9 (24th July 2014) - Lader, Joshua M.; Lam, Geoffrey; Donnino, Robert; Katz, Edward S.; DeAnda, Abe; Ettel, Mark; Saric, Muhamed
Mini‐Abstract We report the case of a 48‐year‐old man with chronic reactive arthritis (previously referred to as the Reiter's syndrome) who presented with a heart failure syndrome due to severe lone aortic insufficiency. The case demonstrates multimodality imaging of the classic cardiac findings associated with the immunogenetic marker HLA‐B27.